O reconhecimento da identidade sexual e de gênero como direito fundamental do indivíduo - Barcellos, Letícia Vasconselos (2018)
This dissertation is linked to the line of research constitutional jurisdiction and democracy. Your problem lies in the recognition of the basic right to free expression of sexual and gender identity. The overall goal of this work is to analyze the effectiveness of current forms of recognition of sexual diversity in Brazil, engendered from the protective judicial action and the implementation of public policies of support to sexual minorities. Its specific objectives consist in examining the process of construction of sexual identity and gender as distinct elements; the sexual liberation and the beginning of the struggle for recognition by means of social movements; the new social actors, with emphasis on LGBTI communities, and their demands for equality and affirmation of their specificities, having as assumptions of the theories about recognition of Nancy Fraser and Axel Honneth. The development of this dissertation occurred from the hypothetical-deductive method, using the method of monographic procedure. The research progressed through bibliographic research, legislative and jurisprudential bases, in addition to the collection of data in electronic sites. The completion of the study allowed us to conclude that, historically, the social struggles by affirmation has generated positive results in society and in the greater observance of fundamental rights. In this context, the liberation of the heteronormative standards with the social mobilisation to require safeguarding the rights of sexual freedom and expression of gender, manifest is a reality of transformations in order to combat the repression, once that demonstrations have boosted the Judiciary, the State and the entities engaged in protecting the LGBTI community, respectively, to make protective decisions, implement programs of recognition of diversity and require greate r assistance to transidentities within their differences, whether in the form of recognition or redistribution, considering that, in accordance with the theory of Nancy Fraser, the effectiveness of justice burden in applying to vulnerable groups recognition and redistribution simultaneously.